2021
DOI: 10.1093/cid/ciab149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Weight and Age on the Pharmacokinetics of Dihydroartemisinin: Food and Drug Administration Basis for Dose Determination of Artesunate for Injection in Pediatric Patients With Severe Malaria

Abstract: For treatment of severe malaria, the WHO recommends 3 mg/kg intravenous artesunate in pediatric patients weighing less than 20 kg. Here we describe FDA’s rationale for selecting 2.4 mg/kg in pediatric patients weighing less than 20 kg based on literature review and independent analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The operation method of Artesunate included oral, intravenous, rectal, and intramuscular injection. There was no significant difference in drug utilization rate among the different methods (Karbwang et al, 1994;van Agtmael et al, 1999;Kitabi et al, 2021). Oral artesunate might be the optimum usage on the basis of its likely higher convenience and economic benefit.…”
Section: Discussionmentioning
confidence: 85%
“…The operation method of Artesunate included oral, intravenous, rectal, and intramuscular injection. There was no significant difference in drug utilization rate among the different methods (Karbwang et al, 1994;van Agtmael et al, 1999;Kitabi et al, 2021). Oral artesunate might be the optimum usage on the basis of its likely higher convenience and economic benefit.…”
Section: Discussionmentioning
confidence: 85%
“…Given that the development and approval of new drugs require substantial investment and time, drug repurposing has gained considerable attention in recent years ( 94 ). For instance, Artesunate has been approved by the FDA for the treatment of severe malaria ( 95 ); rapamycin is an FDA-approved immunosuppressant administered to organ transplantation patients ( 96 ); and Zalcitabine is a nucleoside reverse-transcriptase inhibitor approved by the FDA for HIV treatment ( 97 ). Recent studies have demonstrated their potential to induce ferroptosis and exhibit antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Based on this evidence from PK modeling of data from over 300 children and adults with severe malaria, the World Health Organization (WHO) has recommended parenteral ARS treatment doses of 3 mg/kg for patients weighing < 20 kg (i.e., over 90% of African children with severe malaria) since 2015; a 25% higher dose compared with the 2.4 mg/ kg recommended for children and adults that weigh > 20 kg. 15 Recently, the US Food and Drug Administration (FDA), based on simulated data by Kitabi et al, 16 has challenged this recommendation and suggested that younger children have higher drug exposures, and should therefore not receive an increased dose. Using a population PK model developed by Zaloumis et al, 14 Kitabi et al 16 simulated a virtual pediatric population with severe malaria using US Centers for Disease Control and Prevention (CDC) growth charts, 17,18 and predicted slower clearance and thus increased drug exposure (area under the concentration-time curve (AUC) over 0-12 hours) in children < 10 kg.…”
Section: Study Highlightsmentioning
confidence: 99%
“…15 Recently, the US Food and Drug Administration (FDA), based on simulated data by Kitabi et al, 16 has challenged this recommendation and suggested that younger children have higher drug exposures, and should therefore not receive an increased dose. Using a population PK model developed by Zaloumis et al, 14 Kitabi et al 16 simulated a virtual pediatric population with severe malaria using US Centers for Disease Control and Prevention (CDC) growth charts, 17,18 and predicted slower clearance and thus increased drug exposure (area under the concentration-time curve (AUC) over 0-12 hours) in children < 10 kg. Importantly their simulations assumed that weight (and age) are independent of another important covariate, hemoglobin, which is not the case in malaria endemic countries.…”
Section: Study Highlightsmentioning
confidence: 99%
See 1 more Smart Citation